Why do employees stay despite workplace violence? The roles of job satisfaction and organizational commitment - Meika Kurnia Puji Rahayu Dyah Anggraeni; Lalu Supardin; Mastura Roni (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2026)
Workplace violence is widely recognized as a driver of employee withdrawal and turnover; however, limited evidence explains why employees in labor-intensive industries often remain despite adverse workplace experiences. This study examines the relationships among workplace violence, job satisfaction, organizational commitment, and turnover intention in the Indonesian plantation sector. Using survey data from 354 employees and Partial Least Squares Structural Equation Modeling, the study tests the direct, mediating, and moderating relationships among the constructs. The findings show that workplace violence significantly influences turnover intention and reduces job satisfaction. Job satisfaction partially mediates the relationship between workplace violence and turnover intention, indicating that negative workplace experiences shape employees’ intentions through their evaluation of work conditions. Organizational commitment significantly moderates the violence–turnover relationship, suggesting that highly committed employees may react more strongly to workplace violence due to a greater sense of psychological attachment and perceived betrayal. An unexpected finding indicates that some employees remain despite experiencing workplace violence, suggesting that employees may tolerate such conditions due to economic dependence, limited employment alternatives, income security concerns, and contextual factors that discourage job mobility. These findings contribute to strategic human capital management literature by demonstrating that employee retention may not always signal healthy organizational conditions.